Aloe Vera Mucilage as Drag Reducing Agent in Oil-Water Flow - Abdallah, M. N.; Edomwonyi-Otu, L. C.; Yusuf, N.; Baba, A. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2019)
Drag reduction is the deliberate reduction of the frictional pressure drop in flow systems by the addition of heavy molecular weight polymeric materials as well as other means such as pipeline modifications. Environmentally friendly and cheaper heavy molecular weight polymeric drag reducing agents (DRAs) has become a necessity in the transportation of fluids particularly in the oil and gas industry. However, very few reports exist on the potentials of natural polymers such as extracts from the Aloe Vera plant. In this study, the effects of Reynolds number and polymer concentration on the drag reduction effectiveness of Aloe barbadensis miller were tested. An experimental flow facility using unplasticized Polyvinylchloride (uPVC) pipe of 12 mm ID was constructed with diesel (density = 832 kg/m3, dynamic viscosity = 1.664 mPa.s at 25°C) and water (density = 1000 kg/m3, dynamic viscosity = 0.891 mPa.s at 25°C) as test fluids. Drag reduction as a function of Aloe polymer concentration in the range 50 ppm to 500 ppm and Reynolds number 20000<Re<90000 were investigated by comparing the U-tube manometer pressure drop readings with and without aloe polymer. The pressure drop difference expressed as a percentage of the pressure drop without aloe polymer is termed drag reduction and was used to demonstrate the effectiveness of the Aloe Vera extracts or polymer as a DRA. In single phase horizontal (water) flow, a maximum drag reduction of 64% (U = 4.67 m/s) was measured, while in multiphase horizontal flow, a maximum drag reduction of 53.80% (α = 25%, Um = 4.67 m/s) was measured. Furthermore, measurements showed that pipe inclination had minimal effect on the drag reduction achieved. It was deduced that Aloe Vera mucilage can be used as a drag reducing agent in oil-water flows for Reynolds number below 63,000